The Role of Psychological Capital in Moderating the Influence of Workplace Ostracism on Counterproductive Work Behaviors Through Organizational Cynicism - Ilara Dina Yahya; Susi Haryanti; Wiwiek Rabiatul Adawiyah; Ratno Purnomo (STMIK Indonesia Banda Aceh, 2025)
This study aims to investigate the relationship between workplace ostracism, organizational cynicism, psychological capital, and counterproductive work behavior (CWB). Data were collected through questionnaires distributed to 120 members of the New Indonesian Expedition Cooperative in Wonosobo, Central Java. The study shows that workplace ostracism has a significant negative impact on counterproductive work behavior. Organizational cynicism serves as a significant mediator in the relationship between workplace ostracism and counterproductive work behavior. However, psychological capital does not show a significant moderating role in weakening the impact of organizational cynicism on counterproductive work behavior. The results of this study emphasize the importance of management efforts in addressing workplace ostracism and reducing organizational cynicism to mitigate counterproductive work behavior.